EKRANISASI NOVEL GADIS KRETEK KARYA KAMILA ANDINI DAN DAMPAKNYA PADA PEMBELAJARAN BAHASA INDONESIA SMA - Nelsi, Nelsi; Fitriani, Yessi; Utami, Puspa Indah (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2025)
This research describes various reductions, additions and changes to the story, characters and settings from the novel Girl Kretek by Ratih Kumala to the film Girl Kretek by Kamila Andini and Ifa Ifansyah. This research uses a qualitative descriptive method and uses the novel Kretek Girl by Ratih Kumalas and the film Kretek Girl by Kamila Andini and Ifa Ifansyah as research objects. The data collection technique in this research uses documentation techniques. The data analysis technique used in this research is content analysis. This research obtained the results that the process of white sailing from the novel Girl Kretek by Ratih Kumalake, the film Girl Kretek by Kamila Andini and Ifa Ifansyah experienced several changes which include reducing aspects of the story by 34 events, adding aspects as many as 37 events, and varied aspects of change as many as 8 events. The shrinking aspect of the characters is 19t okoh, the adding aspect is 5 characters, and the changing aspect varies by 1 character. The shrinking aspect of the background is 5 backgrounds, the adding aspect is 7 backgrounds, and the changing aspect is varied by 1 background.